Peran Probiotik Dalam Meningkatkan Pertumbuhan Dan Kesehatan Ikan Lele (Clarias Sp.): Sebuah Studi Literatur - Maestro Laia; Ratna Dewi Zebua (Jurnal Ilmu Pertanian dan Perikanan, 2026)
Catfish (Clarias sp.) is one of the freshwater aquaculture commodities with high economic value and increasing market demand in Indonesia. However, intensive cultivation is often faced with problems of decreased growth performance, low feed efficiency, and high risk of disease infection due to high stocking density. One strategy widely developed to overcome these problems is the application of probiotics in feed and culture media. This article aims to systematically review the role of probiotics on growth, feed efficiency, immune response, and water quality in catfish culture based on a literature study of various national and international scientific publications. The method used is a narrative literature review of publications from 2008-2025 obtained through Google Scholar, Sinta, and indexed international journal databases. The results show that probiotic application, whether from the genus Bacillus, Lactobacillus, or multistrain combinations, consistently improves specific growth rate, reduces feed conversion ratio (FCR), increases survival rate, improves immunological parameters such as phagocytic activity and leukocyte levels, and maintains water quality by suppressing ammonia levels. The appropriate dose and strain type of probiotics are determining factors for application effectiveness.